The Limits of Legal Regulation of Military Relations - E. A. Glukhov (Сибирское юридическое обозрение, 2024)
The paper deals with one of the key features of the regulation of legal relations in the military environment. Those are the detailed regulation of rights, responsibilities, the execution of assigned tasks and orders. The author sees the reasons for such legal expansion in the historical tradition, i.e. fostering obedience and discipline among military personnel, guidance assistance to inexperienced commanders for them to be able to fulfill the assigned duties, as well as controllability and the intention to unify military activities in various military formations. Dysfunctional manifestations of this management style are instilling the lack of independence in decision-making, the habit of relying on superior management for all matters, the loss of initiative by subordinates, the inability to work in a team, lack of immediate response to sudden changes in the situation or non-standard situations. During military operations, these shortcomings not only reduce the effectiveness of control but are also likely to result in prevailing enemy's will, defeat, and unjustified casualties. Using particular examples of excessive regulation, the author questions the need, limits and degree of detailed legal regulation in the military environment. The paper analyzes the cases of directive control of the German Army (Auftragstaktik) and the commander's model used in respect of the subordinates with no detailed orders, with the subordinates being free to choose means and methods to achieve their goals. As measures to improve the legal regulation of the domestic military administration, the paper proposes to eliminate the legal responsibility of military commanders for deviation from detailed orders in cases they take reasonable risk and do not violate legally protected interests. The study uses the methods of formal logic, i.e. comparison, description, classification, analysis, synthesis, etc., which made it possible to characterize the essence of the legal relations under consideration and compare them with the methods of legal regulation of the relevant labor relations.